Establishing Family Folders for Royal Thai Air Force “Thung Sikan Model” - Wanvimonsuk , Gp.Capt. Kanyika; Khamcharoen, Jureeruk; Seehanam, Flg.Off. Nawa (Royal Thai Air Force Medical Gazette, 2024)
Abstract The establishment of the Family Folder for Royal Thai Air Force (RTAF) personnel "Thung SiKan Model," aims to survey and gather data on infrastructure and health status, as well as to enhance the process of providing proactive medical services to RTAF personnel and their families living in the Thung Sikan flats and the area around Don Mueang Railway Station. The data collection includes general and health information and major health problems, which allows for the identification of health problems and the implementation of relevant projects to address these issues based on the community’s needs. As well as the mission of Air Force Medical Department’s “better health services for RTAF” through proactive health promotion and prevention. This model is designed to serve as a prototype for other RTAF communities to establish health registries within their respective areas.